Referenciação e humor em memes do perfil Dilma bolada do Facebook - Lima, Aline Souza de (2019)
In this work, we turn to the textual genre meme with the objective of investigating: i) the (re) construction of discourse objects; ii) the function of referential processes for the production of humor. The choice of this theme is justified due to the relevance of works that seek to characterize meme as a textual genre and the need to investigate referential processes in multisemiotic texts. Thus, it bases on the objectives outline and the selected corpus. We guide in the studies of textual genre as social action (MILLER, 2009, 1994, [1984]; BAZERMAN, 2005, 2006, 2007, 2009; SWALES, 2004, 1992, 1990, ([1984]). About hypertextuality (ELIAS and CAVALCANTE, 2017; BONINI 2011; LIMA, 2013); reference (CAPISTRANO JÚNIOR, 2012, 2017; CAVALCANTE, 2003, 2005, 2011, 2012, 2013, 2017; CAVALCANTE and BRITO, 2014, KOCH and ELIAS, 2009); intertextuality (CAVALCANTE and OLIVEIRA, 2018; CAVALCANTE, FARIA and OLIVEIRA, 2017) and humor (PROPP, 1992; FREUD, 1905; RASKIN, 1985). In terms of textual genre in the digital context, we use the view of (LIMA, 2009; KRESS, 2003; LISBOA, 2010, BAKHTIN, 2010); in the context about Convergence Culture (JENKINS, 2009) and on memes (DAWKINS, 1976, 2001, 2007; MARTINO, 2015; CHAGAS, 2015; SHIFMAN, 2011, 2014; CAVALCANTE and OLIVEIRA, 2018; RECUERO, 2006, 2011). As far as the other possible origins of memes are concerned, we based on (VILLANUEVAMANSILLA, 2017; CARVALHO and KRAMER, 2014; MOUNIN, 1972). Following an analytic bias, this research characterizes as being a qualitative approach and priorizes data analysis, among which were selected eleven memes published on Facebook´s Dilma Bolada profile, during the impeachment process of former president Dilma Roussef. Moreover, what it notes in this research, that humor is constitutive of memes and it has in the texts that were analyzed, the social function of extolling the figure of former head of government Dilma Roussef, as well as, being concerned with denigrating the image of their political rivals